Language Contact, Language Ecology, and Intonational Variation in the Yami Community. (December 2022) - Lai, Li-Fang; Gooden, Shelome
This study investigates socioprosodic variation in Yami, a moribund indigenous language under intense contact with Mandarin in Taiwan: 32 bilingual (Yami-dominant, balanced, Mandarin-dominant) and 5 Yami-monolingual participants were recruited. We used an Interactive Card Game to elicit semi-spontaneous speech for neutral questions (NQ), default declarative questions (DQ1), and declarative questions with lighter incredulity (DQ2). Results reveal that (1) yes/no question intonation in Yami is highly variable; (2) on a broad community level, the DQ1–DQ2 distinction is absent from Yami; and (3) there is prosodic hybridization and innovation in bilingual speech. In particular, we see significant differences in DQ1 and NQ productions, with DQ1s having a rising nuclear configuration, higher pitch level, and wider pitch span, while NQs are realized with a mid-level pattern, lower pitch level, and narrower pitch span. DQ2 utterances exhibited highly varied nuclear configuration patterns with no significant differences in either pitch level or pitch span in DQ1–DQ2 comparisons. Yet, there is evidence that a hybridized DQ2 has begun to be integrated into Yami among younger bilinguals, suggesting that present-day Yami is in flux and is undergoing restructuring. These intonational variations are not easily attributable to a weakened Yami identity. Rather, younger bilinguals, who are leading the change, are highly dedicated to cultural practices and show strong rootedness in their Indigenous identity. Seemingly, while these less fluent speakers no longer use Yami to fulfill their everyday communicative needs, they are leaning more on its socio-indexical functions to reflect their ethnocultural identity.